2017
DOI: 10.3892/etm.2017.4990
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effect of robusta fermented with Leuconostoc mesenteroides in high-fat diet-induced obese mice

Abstract: Abstract. Robusta beans cultivated with Monascus ruber (RMR) were successively fermented with Leuconostoc mesenteroides (LM) and the antiobesity effects were examined. To produce an obese mouse model to investigate the hypolipidemic effects, ICR mice were fed the same high-fat diet for 6 weeks. Treatment groups were given 10 or 20% RMR-LM. Body weight changes in the 20% RMR-LM group were lower compared with those in the control group. Visceral adipose tissue weight and adipose size were significantly lower in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, Soypro treatment reduced low density lipoprotein cholesterol (LDL) levels without affecting body weight in obese rats [ 25 ]. Another study reported that pear extract and robusta fermented with L. mesenteroids significantly reduced body weight and adipose tissue mass, and the size of lipids in liver in obese rats compared to control rats [ 27 , 33 ]. Supplementation with L. mesenteroids reduced blood urea nitrogen, glucose, and triglyceride levels in obese mice serum, as well as fatty liver development and liver steatosis in comparison with controls [ 26 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Soypro treatment reduced low density lipoprotein cholesterol (LDL) levels without affecting body weight in obese rats [ 25 ]. Another study reported that pear extract and robusta fermented with L. mesenteroids significantly reduced body weight and adipose tissue mass, and the size of lipids in liver in obese rats compared to control rats [ 27 , 33 ]. Supplementation with L. mesenteroids reduced blood urea nitrogen, glucose, and triglyceride levels in obese mice serum, as well as fatty liver development and liver steatosis in comparison with controls [ 26 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that L. mesenteroides plays significant roles in fermentation of foods, such as sauerkraut from Europe and kimchi from East Asia ( Beganovic et al, 2011 ), and it contributes to the improvement of the nutritional and organoleptic properties of fermented foods. In addition, L. mesenteroides is also widely used in the field of in the biochemical and pharmaceutical industries ( Choi et al, 2017 ). The demand for producing high quality dextran and their derivatives continues increasing all over the world ( Naessens et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%